Valuasi Objek Wisata Kebun Raya Lemor Menggunakan Contingent Valuation Method (CVM) Tahun 2020 - Afifudin Afifudin; Hindy Ikhwana; Wahyu Khalik (Jurnal Pariwisata Nusantara (JUWITA), 2022)
Lemor Botanical Garden Attraction is a Tourist Attraction located in Cempaka Hamlet, Suela Village, Suela Subdistrict, East Lombok Regency, West Nusa Tenggara become one of the tourist destinations that have visitors who continue to increase every year, but because covid 19 cases decrease in 2020. The problem faced is the lack of facilities in Lemor Botanical Garden Attractions compared to what is needed so that the management is less than optimal. This research was conducted to find out the factors that affect the desire to pay (WTP) from visitors to Lemor Botanical Garden Attractions and to find out the value of Lemor Botanical Garden Attractions with Contingent Valuation Metohod (CVM). This research method compares quantitative methods with multiple linear regression analysis tools, where the desire to pay (WTP) as a dependent variable, while income, education, and dummy origin as independent variables. The results showed that the variable income, education, and dummy origin were equally positive and significant to the desire to pay (WTP). The value of the desire to pay (WTP) of the average visitor of Lemor Botanical Garden Attraction Rp14,388,0597 with the number of visitors in 2020 as many as 10,590 people so that the value of Lemor Botanical Garden Attraction in 2020 is Rp152,369,552.